2017
DOI: 10.3233/jhd-170255
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced retinal responses in Huntington’s disease patients

Abstract: ERG studies revealed significantly altered retinal responses at multiple flash intensities in subjects with an HD expansion allele compared to controls. Significant differences were observed with either light-adapted tests or the dark-adapted red flash which suggests that the enhanced responses in HD patients is specific to the cone photoreceptor pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…This is because GEE can account for the correlation structure that results from repeated measurements of the same individual, leading to more consistent estimation of differences when compared to parametric tests that neglect correlation [46]. Others have used GEE to assess differences over time in human retinal ERG outputs, which are similar in nature to ABR progressions [47,48]. Of course, this method is only valid when thresholds are not statistically different, as we had found for the 32 kHz frequency (Fig 2).…”
Section: Discussionmentioning
confidence: 99%
“…This is because GEE can account for the correlation structure that results from repeated measurements of the same individual, leading to more consistent estimation of differences when compared to parametric tests that neglect correlation [46]. Others have used GEE to assess differences over time in human retinal ERG outputs, which are similar in nature to ABR progressions [47,48]. Of course, this method is only valid when thresholds are not statistically different, as we had found for the 32 kHz frequency (Fig 2).…”
Section: Discussionmentioning
confidence: 99%
“…We have created a list of several neurodegenerative diseases (Table 4.1) that collectively affect a considerable proportion of the population, and in which retinal alterations have been demonstrated. Preliminary studies suggest that several other conditions not included here, including Huntington´s disease, stroke, and psychiatric disorders, have manifestations in the retina 3,[11][12][13][14] . The fact that these alterations are common to so many neurodegenerative conditions underscores the need for further studies to better understand the impact of CNS neurodegeneration on the retina.…”
Section: Retinal Alterations In Neurodegenerative Conditions Of the Bmentioning
confidence: 91%
“…Although Knapp et al [18] report findings from a single case study, it is of note that reduced ERG amplitudes are in keeping with results from mouse models of Huntington's Disease [19]. Moreover, a key difference between the two studies is that whereas Knapp et al [18] report data from an unmedicated premanifest subject, Pearl et al [17] report data from a group of HD-manifest patients. Some medications prescribed to HD patients, such as haloperidol have been shown to enhance ERG amplitudes in non-human primates, causing them to appear normal [20].…”
Section: The Retinamentioning
confidence: 96%
“…More recently, two studies have examined the possible effects of HD on the retina using electroretinograms (ERGs). Pearl et al [17] 1 Eye movement dysfunction is beyond the scope of this review and is comprehensively reviewed elsewhere [12,13,14] reported increased ERG amplitudes across a range flash intensities but there no differences in their latency. Conversely, Knapp et al [18] reported reduced ERG amplitudes in single case study of a 25 year old asymptomatic gene carrier with no differences in latencies.…”
Section: The Retinamentioning
confidence: 99%